Risk of recurrence after a first seizure and implications for driving: further analysis of the Multicentre study of early Epilepsy and Single Seizures. (7th December 2010) - Bonnett, L J; Tudur-Smith, C; Williamson, P R; Marson, A G
Abstract : Objective To determine for how long after a first unprovoked seizure a driver must be seizure-free before the risk of recurrence in the next 12 months falls below 20%, enabling them to regain their driving licence. Design Randomised controlled trial: Multicentre study of early Epilepsy and Single Seizures (MESS). Setting UK hospital outpatient clinics from 1 January 1993 to 31 December 2000. Participants People entered MESS if they had had one or more unprovoked seizures and both the participant and the clinician were uncertain about the need to start antiepileptic drug treatment. The subset of people used for this analysis comprised participants aged at least 16 years with a single unprovoked seizure. Main outcome measure Risk of seizure recurrence in the 12 months after a seizure-free period of 6, 12, 18, or 24 months from the date of the first (index) seizure. Regression modelling was used to investigate how antiepileptic treatment and several clinical factors influence the risk of seizure recurrence. Results At six months after the index seizure the risk of recurrence in the next 12 months for those who start antiepileptic drugs was significantly below 20% (unadjusted risk 14%, 95% confidence interval 10% to 18%). For patients who did not start treatment the risk estimate was less than 20% but the upper limit of the confidence interval was greater than 20% (18%, 13% to 23%). Multivariable analyses identified subgroups with a significantly greater than 20% risk of seizure recurrence in the 12 months after a six month seizure-free period, such as those with a remote symptomatic seizure with abnormal electroencephalogram results. Conclusion After a single unprovoked seizure this reanalysis of MESS provides estimates of seizure recurrence risks that will inform policy and guidance about regaining an ordinary driving licence. Further guidance is needed as to how such data should be utilised; in particular, whether a population approach should be taken with a focus on the unadjusted results or whether attempts should be made to individualise risk. Guidance is also required as to whether the focus should be on risk estimates only or on the confidence interval as well. If the focus is on the estimate only our unadjusted estimates suggest that treated and untreated patients are eligible to drive after being seizure-free for six months. If the focus is also on confidence intervals, direction is needed as to whether a conservative or liberal approach should be taken. Trial registration Current Controlled Trials ISRCTN98767960 .